Implikasi Ke-hujjah-an Hadis Mursal Perspektif Ibn Hazm Al-Andalusiy - Damayanti, Amelia (Al-Bukhari : Jurnal Ilmu Hadis, 2023)
It is known that the authenticity of the Mursal Hadith is debated by several hadith scholars. The majority of muh{addiṡ have agreed that the Mursal Hadith has been designated as a da‘if hadith because there is a disconnected sanad or inqita' and the narrators of the hadith are unknown or majhul. In this article, we will focus more on the Hadith scholar figure from Andalusia, namely Ibn Hazm. Ibn Hazm is a hadith scholar who is known for having strict judgment in assessing a hadith. This he did because he was very careful to maintain the authenticity of the Prophet's hadith. So he has different criteria with other hadith scholars. The type of research used in this article is library research with a qualitative research model because with this type and model the authors obtain detailed and accurate data. The purpose of writing this article is to find out how the definition of Mursal Hadith is from Ibn Hazm's point of view, so that we can compare the difference between the definition of Mursal Hadith according to Ibn Hazm and the majority of hadith scholars and to know the implications of the authenticity of the Mursal Hadith from Ibn Hazm's perspective. The results of the study show that Ibn Hazm firmly rejected the narration of the Mursal Hadith and this of course had an impact on some of the narrations of the hadith which were narrated in a mursal.